Demographic, Clinical, and Antibiotic Exposure Factors Associated with Carbapenem-Resistant Acinetobacter baumannii: An Eight-Year Retrospective Study - Angky Budianti; Dzaki Fadlurrahman Ayyasy; Mubarokah Mubarokah; Victor Sitorus; Yulia Rosa Saharman; Budiman Bela; Anis Karuniawati (Jurnal Kesehatan dan Kedokteran, 2026)
Antimicrobial resistance is a major global health challenge, and carbapenem-resistant Acinetobacter baumannii (CRAB) is of particular concern because of its high level of resistance, limited therapeutic options, and substantial burden in healthcare-associated infections. Identifying patient characteristics and antibiotic exposure associated with CRAB is essential to support effective antimicrobial stewardship and infection prevention strategies. Objective: This study aimed to analyze the association of demographic factors, including age and comorbidities, clinical diagnosis or manifestations, and a history of carbapenem use within the previous month with CRAB among clinical isolates examined at the Clinical Microbiology Laboratory, Faculty of Medicine, Universitas Indonesia, during 2017–2024. Methodology: This quantitative study employed a retrospective cross-sectional design using secondary laboratory and clinical data. Samples were selected through total sampling from patients with clinical specimens yielding A. baumannii. Descriptive analysis was used to characterize the study population, while Chi-square tests were applied to assess associations between the investigated factors and carbapenem resistance. Findings: A total of 172 A. baumannii clinical cultures were identified, of which 118 (68.6%) were CRAB. Age was significantly associated with CRAB (p=0.004), with patients aged >59 years representing the largest CRAB group. Clinical diagnosis or manifestation was also significantly associated with CRAB (p=0.005), with respiratory tract infection being the most frequent manifestation. Previous carbapenem use within one month was significantly associated with CRAB (p=0.009), with an odds ratio of 8.33 (95% CI: 1.48–46.94). In contrast, comorbidity was not significantly associated with CRAB (p=0.665). Implications: These findings support strengthening antimicrobial stewardship, particularly the appropriate use and continuous evaluation of carbapenem therapy, alongside enhanced surveillance and infection prevention measures among high-risk patients. Originality: This study provides local epidemiological evidence from an eight-year clinical dataset and integrates demographic, clinical, and previous carbapenem-exposure factors to characterize CRAB at a clinical microbiology laboratory in Jakarta, thereby contributing institution-specific evidence for CRAB surveillance and prevention strategies.